DISEMINASI TEKNOLOGI PENGOLAHAN SAMPAH TERPADU DI KABUPATEN PURWOREJO - Indrawati, Rosiana; Hindarti, Fifin; Puspitasari, Amallia (Sekolah Tinggi Teknologi Adisutjipto, 2020)
Household waste is one of the sources of waste which has a big role in environmental pollution. The community as a waste producer still lacks a high level of concern for waste management itself. Partners in this case are Bandungrejo Village Youth and Youth Youth Association of ?Jaya Jaya? RT 02 RW 04 Bandungrejo Village Bayan District Purworejo District initiative to be able to manage the waste they produce so that it is not harmful to the environment while at the same time adding value to the income from the sale of processed waste. So in this case, the proposer has ideas to develop waste processing technology that can be utilized by partners in this case the community through the Appropriate Technology Application Program (PPTTG) in collaboration with the Ministry of Research, Technology and Higher Education with the House of Representatives Commission X. Activities undertaken i.e. to provide assistance in the form of an integrated waste processing machine as well as a waste management training. The tools provided include one unit of a plastic chopper machine, one unit of an organic chopper machine, one unit of an organic sieving machine, 20 unit of sorted waste bins, 20 units of composter and financial assistance for the construction of a waste processing building for the placement of these machines. This activity is expected to solve the problems of partners in waste management and improve the welfare of the community itself.